2013
DOI: 10.1063/1.4856975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti seed layers on structure of self-organized epitaxial face-centered-cubic-Ag(001) oriented nanodots

Abstract: Epitaxial Ag(001) grown on MgO(001) and TiN(001): Twinning, surface morphology, and electron surface scatteringThe influence of Ti seed layers on the structure of self-organized Ag nanodots, obtained with a Ti seed-layer-assisted thermal agglomeration method, has been investigated. The samples were grown on MgO(001) single crystal substrates by RF magnetron sputter deposition. The samples were deposited at room temperature and post-annealed at 350 C for 4 h while maintaining the chamber vacuum conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…For a 6.0-nm-thick Ag layer with a 1.0-nmthick Ti seed layer, the surface morphology of the Ag layer transformed into separate island structures, leading to the formation of a nanodot array [Fig. 1 Compared with the case of the MgO(100) substrate, as reported previously, 11,12) the nanodots observed in this study are slimmer. Thus, the Ag=Ti surface structure formed on the MgO(110) substrate is a type of "nanorod".…”
supporting
confidence: 65%
See 2 more Smart Citations
“…For a 6.0-nm-thick Ag layer with a 1.0-nmthick Ti seed layer, the surface morphology of the Ag layer transformed into separate island structures, leading to the formation of a nanodot array [Fig. 1 Compared with the case of the MgO(100) substrate, as reported previously, 11,12) the nanodots observed in this study are slimmer. Thus, the Ag=Ti surface structure formed on the MgO(110) substrate is a type of "nanorod".…”
supporting
confidence: 65%
“…Recently, we have reported on seed-layer-assisted agglomeration (SLAA), a unique technique for the fabrication of agglomerated Au or Ag nanodots, which overcomes the constraints of thermodynamics. [10][11][12] We demonstrated that the insertion of an ultrathin Fe or Ti seed layer between the MgO(001) substrate and a thin Au or Ag layer promoted agglomeration at a relatively low temperature. We also observed that the epitaxial growth of the agglomerated Ag nanodots on the MgO(001) substrate was facilitated by the use of the Ti seed layers.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Nanoparticles are well-known for their enhanced physical and chemical properties over their bulk counterparts with the added possibility to manipulate these properties for a range of different applications by simply varying their dimension and geometry. , The integration of nanoparticles into one-, two-, or three-dimensional (2D or 3D) structures leads to novel collective properties that can be controlled by altering the nanoparticles’ arrangements, which in turn influences their cooperative interactions. Therefore, the development of functional nanostructures with specific patterns and high interstitial long-range order has received considerable interest in recent years due to their applications in the fields of solar cells, optical devices, chemical sensing, and catalysis . From a chemical sensing point of view, it is important to consider not only high sensitivity but also uniformity and reproducibility of the surface (sensitive layer) itself.…”
Section: Introductionmentioning
confidence: 99%
“…Kamiko et al recently reported self-organized epitaxial nanostructures caused by the thermal agglomeration of a Ag film with a thin Ti seed layer. 22,23 We previously used a ZnO film with a crystalline (001) orientation as a seed layer to improve the crystalline orientation of an fcc-Ag (111) underlayer. 21 Thus, it is likely that the ZnO layer inserted into the Ag/Ru interface promotes the surface metal agglomeration of fccAg with a crystalline (111) orientation.…”
mentioning
confidence: 99%